Catching up of emerging economies: The role of capital goods imports, FDI inflows, domestic investment and absorptive capacity - Alexander Glas; Michael Hübler; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2015)
We assess the role of capital goods imports and inflows of foreign direct investment (FDI) as transmission channels through which major emerging economies (BRICs, i.e., Brazil, Russian Federation, India and China) could catch up with advanced source countries in terms of total factor productivity (TFP). We find that the importance of these transmission mechanisms depends on the BRICs' local capacity to absorb superior technologies and on domestic investment.
Keywords: F14; F21; O47; 330; total factor productivity; imports; foreign direct investment; absorptive capacity; BRICs